Review paperWhy the mother’s immune system does not reject her fetus - Cadili, Ali (Archives of Medical Science, 2008)
Fetal antigens are allogeneic to the mother’s immune system and should theoretically elicit an immune response. The fact that this does not occur and that the fetus thrives for so long in the mother without undergoing rejection by her immune system is a scientific mystery. There are five main theories that could explain the fetus’s success in evading the mother’s immune system. These are the mother’s overall immune suppressed state, maternal tolerance to fetal antigens, down-regulation of fetal antigens, the presence of a barrier between maternal immunity and the fetus, and local immune suppression at the site of the placenta. None of these mechanisms can fully explain this phenomenon despite the varying degrees of evidence in support of each. The last mechanism (local immune suppression) seems to be the most plausible one according to current thinking. The actual explanation of this paradox may well lie in a combination of several different factors rather than a single account.